The housing issue and Planning in the city of Niterói – RJ (Brazil) in the early 1970s: contradictory aspects of a Master Plan - Silva, Maria Lais; Corrêa, Mariana; Santos, Bruna (International Planning History Society Proceedings, 2016)
This paper is part of a more comprehensive research developed by the authors at Universidade Federal Fluminense and entitled “Housing, plan, city: the housing issue in the city of Niterói and the process for the master plan (1960 – 1975)”. The above research aims to analyse the origin and development of the favelas of Niterói-RJ (Brazil) in several dimensions, including how the housing situation occurs in the city planning process. In the case of this paper, it was considered the Master Plan elaborated by Wit-Olaf Prochnik’s office (1975-1977) that was preceded by large data collection and prospections that were base for an extensive list of proposals and projects. The purpose of this paper was to discuss two issues that represented, somehow, contradictory aspects related to the plan structured by the planning office. The first issue comes from the fact that it occurred an intensification of favela growth in the city of Niterói, especially in the 1960s and the 1970s, along with the forced removal of more than one thousand families mainly to other municipalities, due to the construction of the Rio- Niterói Bridge. At the end of the 1960s, it was observed a growth of the favelas whose residents came to represent about 7% of the total of the city population; the settlements were spread over hills and government’s lands. At the same time the real estate market that had already been developing in the previous decade grew in dimension and aggressiveness. In this same period, it was implemented a national housing policy by the Banco Nacional de Habitação (BNH) and was created the Companhia de Habitação do Estado do Rio de Janeiro (COHAB-RJ), highlighting the housing issue. It’s important to consider that the national and local policy included the building of social housing with the removal of favelas. In spite of the dramatic situation, the reference of social housing in the master plan then elaborated is small, mainly pointing to general guidelines. On the other hand, the plan itself presented aspects both “traditional” and “innovative”: in its methodology and broader proposals, it follows the planning guidelines of the authoritarian military regime, based on the Serviço Federal de Habitação e Urbanismo (SERFHAU). However, it “rehearses” other methods, seeking a type of participation of the local agents, with seminars open to the population in the phase of elaboration and discussion of the plan, aiming different alternatives of urban development. Thus, the hypothesis developed was that the Wit-Olaf Prochnik’s Master Plan presented evidences of a possible but still “shy” transition in the planning process, apparently taking into account the particularities of the city of Niterói. Besides the existing bibliography, the methodology included primary sources, particularly documents of the municipality, the press (newspapers published between 1960 and 1975), and interviews with experts and technicians that worked in the Plan or were somehow related to the municipality of Niterói.